Projecting progress toward the Millennium Development Goals - Howard White; Nina Blöndal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The Millennium Development Goals have become the frame of reference for most of the development community: the standard by which performance will ultimately be judged. Given their importance, considerable attention has been paid as to whether these goals will be met or not. The overwhelming conclusions from such analyses are not positive. The goals will not be met. There are exceptions-education has expanded rapidly, although questions are raised about quality, and some countries, notably in South East Asia, but also South Asia to a lesser extent, have done well across the board and will meet several of the goals. But many countries, most especially in Africa, will not. The projections show that poverty will become more heavily concentrated in Africa in both relative and absolute terms. In addition, whilst urban poverty will increase, in 2015 poverty will remain a predominately rural phenomenon, with 60-70 per cent of the poor (depending on the measure) living in rural areas. But these projections are based on assumptions, including the assumption of business as usual. Various adverse shocks may result in far worse scenarios. On the other hand, more intensive promotion of pro-poor policies can mean that the goals might yet be realized.
Keywords: I0; I30; I32; 330; Millennium Development Goals; poverty projections; mortality; nutrition; poverty; education; health; inequality; Millennium Development Goals